Bioactive Compounds of Insulin Leaves (Smallanthus sonchifolius) as DPP4 Enzyme Inhibitors in Insulin Signaling Mechanism for the Treatment of Type 2 Diabetes Mellitus: In Silico Study - Wardani, Intan Kusuma; Aulia, Winni Nur; Saputro, Anjar Hermadi; Ainiya, Aliva; Mariska, Soraya; Kamilaini, Diva Arisanti; Vega, Amelia; Maharani, Ayu Puspita; Fransisca, Ni Putu Vina (Chimica et Natura Acta, 2025)
Type 2 Diabetes Mellitus (DM) is characterized by a relative insulin deficiency caused by pancreatic cell dysfunction and insulin resistance. Herbal-based traditional medicine can be an alternative, one of which is insulin leaf (Smallanthus sonchifolius), which has antidiabetic effects and can lower blood sugar levels by inhibiting glycogenolysis and gluconeogenesis. DPP4 inhibitors are a class of antidiabetic drugs used in the treatment of type 2 DM. This study aims to analyze and predict the binding patterns of flavonoid derivatives from insulin leaf (Smallanthus sonchifolius) compounds to the DPP4 enzyme inhibitor, to determine the binding affinity of these compounds to the target protein as an antidiabetic agent. The study was conducted using an in silico method, utilizing the Research Collaboratory for Structural Bioinformatics (RCSB), Avogadro Software, AutoDockTools (version 1.5.6), and Biovia Discovery Studio 2021 for molecular docking and prediction of binding patterns and affinity for the DPP4 N7F protein. The results of this study showed that the binding energy value obtained from the natural ligand N7F was -11.0 kcal/mol. The binding energy value for 1,19-dihydroxy-2,6,10,14-phytateraen-18-oic-acid with the N7F protein was -9.8 kcal/mol. Therefore, 1,19-dihydroxy-2,6,10,14-phytateraen-18-oic-acid has a more stable binding with the DPP4 enzyme N7F target protein. Based on the results obtained from molecular docking of the flavonoid derivative compounds from insulin leaf (S. sonchifolius), the compound 1,19-dihydroxy-2,6,10,14-phytateraen-18-oic-acid  showed the most potential as a DPP4 enzyme inhibitor among the other compounds.